El juego táctico y su incidencia en la práctica de los deportes de conjunto en los niños de las escuelas fiscales del barrio Zalapa del cantón Loja. Propuesta curricular. Año 2012 - 2013 - Quizhpe Guaman, Wilson Gustavo (2015)
The theme developed in the research, analyzed the tactical game and its impact on the practice of team sports in children from public schools of Zalapa neighborhood of Canton Loja. Curricular Proposal, whose problems are determined in Curriculum into force of the Course of Physical Education, through the Block No. 2 Games does not allow the process of learning of the physical fundamentals - Technical team sports, for lack of a tutorial practice over the lack of guidelines for teachers to facilitate classroom teaching team sports from the perspective of improving learning outcomes; and not coming teaching team sports in physical education classes for lack of specialized teachers, limited time and lack of infrastructure and adequate and proper implementation, coos objectives are aimed to analyze whether the Curriculum in force does not allow the process of learning of physical principles - technical team sports, for lack of a tutorial practice in children; likewise, whether the lack of guidance on classroom teachers, does not provide the teaching of team sports and determine whether the lack of specialized teachers, infrastructure and proper implementation, is affecting the learning of the team sports, just as the Review of Literature organized into the following variables is detailed: fundamentals, technical foundations, curriculum Games and team sports; The methods used were: the method of analysis and synthesis; inductive - deductive; the heuristic method and statistical method. The techniques used were the physical test, technical test, survey of 6 teachers and 56 students, more than direct observation. The working hypothesis developed are: The Curriculum in effect, does not allow the process of learning of the physical fundamentals - Technical team sports; similarly, the lack of guidelines on classroom teachers, not facilitate the teaching of team sports; and the lack of specialized teachers, infrastructure and proper implementation, is affecting the learning of team sports in physical education classes with children in public schools: José Rafael Vega and Ramón Arízaga Zalapa Burnet neighborhood of Canton Loja. Academic year 2012 - 2013; the following relevant conclusions were determined: The Curriculum in force, does not allow the process of learning of the physical fundamentals - Technical; and the lack of guidelines on classroom teachers, does not facilitate the teaching of team sports; and lack of specialized teachers, infrastructure and proper implementation, is itself influencing the learning of team sports; with which he made the following recommendations: that teachers consider the Alternative Curriculum proposed to improve the teaching-learning process. The structures of the alternative proposal were structured by objectives, stages of education and develop skills in teaching whole games.